THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL ATTITUDE ON FINANCIAL RESILIENCE OF MICRO, SMALL, MEDIUM ENTERPRISES (MSMES) IN MANADO - Hanelisty Diona Chicha Korompis; David Paul Elia Saerang; Shinta Jeanette Camelia Wangke (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
This study aims to analyze the influence of financial literacy and financial attitude on financial resilience of Micro, Small, Medium Enterprises (MSMEs) in Manado. The quantitative approach used in this research, where research is conducted by collecting questionnaire data from 65 MSME actors who have featured products in Manado. The method used to analyze the influence of independent variables toward the dependent variable is multiple regression analysis. The results of this study indicate that financial literacy have a positive and significant effect on financial resilience, while financial attitude is also had a positive and significant effect on financial resilience. This research also indicates that simultaneously, financial literacy and financial attitude positively and significantly influence financial resilience of MSMEs in Manado.   Keyword: financial literacy, financial attitude, financial resilience